Informação e tecnologia para implantação do agroturismo em Echaporã - SP - Pinto Junior, Wellington Correia [UNESP] (2005)
The information transformed in knowledge, contextualized and potentialized by the use of new technologies, is the fastest way for the sustainable development and the diferential competiveness of many comunities. This process is the main force of the tourist segment, one of the sections of the economy which has presented the widest growth in the world, according to data of the World Tourism Organization, dealing approximately with $ 4,5 trillions a year and generating 190 millions of employments 10,6% of the world work force. In Brazilian districts where tourism activity is strategically planned with a wide participation of the comunities, tourism becomes an important economic and sustainable alternative. In a place where social, environmental and economical impacts occur, damages are irreversible. Through the accomplisment of the Inventory of the Tourist Offer in Echaporä (SP), there was a search to identify the units of rural production and tourist potential of the district, in order to make the productive arrangement of the place. Echaporä has faced serious economical and social problems. This work proposes the implantationof agrotourism as an alternative source of income, employment and sustainable development for the district following the model of the one implanted in Venda Nova Do Imigrante(ES), national reference in this tourism in rural area.In that way, it was chacterized the technology and administration management of information as well as its prepoderant role in the development of the tourism. Specific information supported by specific literature ans visits in loco were used as references to experiences in Venda Nova Do Imigrante(ES), in order to elaborate the process and develop actions and public policies related to tourism in Echaporä. The theoretical information available in this work relates the technological information and its interations to... (Complete abstract, click electronic access below)